Mass measurements of neutron-rich Rb and Sr isotopes - Klawitter, Renee; Bader, A.; Brodeur, Maxime; Chowdhury, U.; Chaudhuri, A.; Fallis, J.; Gallant, Aaron; Grossheim, A.; Kwiatkowski, A. A.; Lascar, D.; Leach, K. G.; Lennarz, A.; et al. (Physical review. C, Nuclear physics, 2016)
We report on the mass measurements of several neutron-rich Rb and Sr isotopes in the A≈100 region with the TITAN Penning-trap mass spectrometer. By using highly charged ions in the charge state q=10+, the masses of 98,99Rb and 98-100Sr have been determined with a precision of 6-12 keV, making their uncertainty negligible for r-process nucleosynthesis network calculations. The mass of 101Sr has been determined directly for the first time with a precision eight times higher than the previous indirect measurement and a deviation of 3σ when compared to the Atomic Mass Evaluation. We also confirm the mass of 100Rb from a previous measurement. Furthermore, our data indicate the existence of a low-lying isomer with 80keV excitation energy in 98Rb. We show that our updated mass values lead to minor changes in the r process by calculating fractional abundances in the A≈100 region of the nuclear chart.